An Exploration of Sleep and Family Factors in Young Children at Familial Risk for ADHD. Issue 6 (2nd November 2021) - Keating, J.; Bramham, J.; McNicholas, F.; Carr, A.; Hasshim, N.; Downes, M.
ABSTRACT: Objective : The aim of the current study was to examine relations between sleep problems and family factors and early markers of ADHD in young children with and without a familial risk for ADHD. Methods : Differences in sleep behavior and family functioning in children under 6 years with (n = 72) and without (n = 139) a familial risk for ADHD were investigated. The influence of family and sleep factors on the development of early temperament markers of ADHD (effortful control and negative affect) was explored. Parents/caregivers completed questionnaires on family functioning, child sleep behavior, and general regulatory behaviors. Results : A significant difference was observed between high-risk and low-risk groups for family functioning in the infant/toddler (<3 years) and preschool (>3 years) cohorts. Parents of infants/toddlers in the high-risk group reported poorer infant sleep. However, there were no sleep differences reported for the preschool cohort. Family functioning was found to predict effortful control, while sleep quality predicted negative affect. Conclusion : The results of this study highlight potential family and sleep issues for young children with a familial history of ADHD and the potential influence of these factors on early temperament markers of ADHD. Future research should explore these relations further in order to better establish whether early sleep and family interventions could mitigate later ADHD symptomatology.